PREVALENCE OF ACUTE KIDNEY INJURY IN TROPICAL ACUTE FEBRILE ILLNESS AND ITS OUTCOME IN A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Behera, Bijaya Kumar; Kumari, Preety; Khatua, Sasmita (Student’s Journal of Health Research Africa, 2024)
Background Tropical acute febrile illness (TAFI) accounts for the majority of hospitalizations in our country. It is one of the most frequent causes of acute kidney injury (AKI) leading to very high morbidity and mortality in the Indian sub-continent. This study was conducted to evaluate the prevalence and outcome of AKI associated with TAFI. Methods This observational study was carried out on 100 patients of TAFI belonging to the age group of 15-89 years of both genders, admitted in the medicine ward fulfilling the inclusion and exclusion criteria in a tertiary care government teaching hospital in Eastern Odisha, India from June 2021to October 2022. After obtaining informed consent, they were thoroughly evaluated for clinical signs and symptoms along with routine laboratory investigations. Kidney Disease Improving Global Outcomes (KDIGO) criteria were followed for AKI diagnosis and classification. Outcomes in terms of duration of hospital stay, treatment with dialysis, the requirement for intensive care unit (ICU) support, survival, and mortality were analyzed and recorded. Results Out of 100 patients of TAFI, 58% of patients developed AKI among whom 20 (34.4%) patients required hemodialysis. The majority (77.6%) of AKI patients improved, around 15.5% of patients progressed to chronic kidney disease (CKD) and mortality was seen in about 6.8% of patients Conclusion The spectrum of TAFI in this present study shows malaria (38%) followed by dengue (27%), scrub typhus (16%), and leptospirosis (12%). The most common etiology of AKI in TAFI is leptospirosis (75%). Recommendations Recommendations include early diagnosis and management of tropical acute febrile illness (TAFI) and acute kidney injury (AKI), preventive measures targeting common causes, and a multi-disciplinary approach to patient care to reduce morbidity and mortality in tropical regions.